PENGARUH PEMIJATAN PERINEUM PADA IBU HAMIL TRIMESTER III TERHADAP KEJADIAN RUPTUR PERINEUM SAAT PERSALINAN DI BPM SUHESTI KOTA MEDAN KECAMATAN MEDAN DELI TAHUN 2022 - Siti Amalia; Ninsah Mandala Putri Sembiring (Akademi Analis Kesehatan Pekalongan, 2022)
Perineal rupture can occur due to spontaneous tears or episiotomy. The incidence of perineal rupture in primigravidas is more than in multigravidas. This study aims to determine the effect of Perineal Massage in Trimester III Pregnant Women on the Incidence of Perineal Rupture during Childbirth BPM Suhesti Medan City, Medan Deli District in 2022. This type of research is an analytical survey with a cross sectional method approach. The number of samples used was 40 people. The data analysis technique uses the Chi Square test. the results obtained from 40 respondents, the results obtained were p = 0.003, so there was an effect of perineal massage in third trimester pregnant women on the incidence of perineal rupture during childbirth.